An empirical study of the challenges facing zakat and waqf institutions in Northern Nigeria - Mahadi Ahmad (ISRA International Journal of Islamic Finance, 2019)
Purpose: The purpose of this paper is to unearth the factors inhibiting the development of zakat (the Islamic obligatory alms) and waqf (endowment) institutions in Northern Nigeria, with the aim of proffering appropriate solutions. Design/methodology/approach This paper uses a qualitative research methodology whereby data was sourced from relevant stakeholders in Northern Nigeria. To select the appropriate interviewees, maximum variation and homogenous Purpose:ful sampling techniques were used. Findings The findings of the paper show that zakat and waqf institutions in Northern Nigeria have not achieved their inherent Sharīʿah objectives because members of the public have little or no trust or confidence in the institutions. Also, the potential zakat payers and waqf donors dislike political office holders' involvement in the appointment of the institutions' administrators. Finally, the administrators lack adequate managerial and administrative knowledge of the two institutions. Research limitations/implications The current research focusses on causes of low performance of zakat and waqf institutions solely in Northern Nigeria. It is envisaged that subsequent researchers may conduct research on the possibility of having a federal law that will strengthen the overall establishment and development of zakat and waqf in Nigeria. This will affect both Muslim-majority and Muslim-minority communities. Originality/value This paper represents a referenceable work in the field of zakat and waqf in Northern Nigeria, as it uses an approach that sources primary data in the form of participants' point of view instead of relying on literature or document analysis. It is not a mere theoretical study of the literature but an empirical investigation of the problem.
Keywords: 330; Confidence; Waqf; Trust; Zakat; Northern Nigeria; Homogeneous; Maximum variation